Accelerometers in collars identify behavioral states in captive African elephants Loxodonta africana - Soltis, J; Wilson, RP; Douglas-Hamilton, I; Vollrath, F; King, LE; Savage, A (Inter-Research Science Center, 2012)
Accelerometers are motion-detection devices that, when attached to animals, are capable of detecting body orientation, overall activity levels, and specific behavior patterns. We deployed accelerometers in order to study the hypothesis that accelerometer output would allow us to distinguish between 4 behavior patterns in 3 adult female African elephants Loxodonta africana at Disney’s Animal Kingdom®, Florida, USA. Tri-axial accelerometer data loggers were attached to the tops of collars worn around the elephants’ necks. Behavior was documented on video while the accelerometer output was stored on the data logger. Feeding, bathing, and walking behaviors were recorded in all 3 subjects, while swaying behavior could be recorded in only 1 subject. Data in the 3 physical dimensions (sway, surge, and heave) were analyzed in terms of overall magnitude of movement (dynamic acceleration) and in terms of the periodicity of movement. When classifying accelerometer data of unlabeled origin to the correct behavioral state, overall success ranged from 70 to 91%. Bathing was sometimes confused with feeding and walking, but feeding, walking, and swaying were easily distinguished from each other. These results show that data from accelerometers can distinguish an elephant’s behavioral states, and thus may be used to monitor elephant behavior remotely. Such devices could be deployed for a variety of purposes, ranging from monitoring elephant activity in zoos to an early-warning system that could alert the authorities when wild elephants are being illegally hunted.